Examining the Article Anti-religious Radicalism in Law Number 18 of 2019 concerning Pesantren - Ghofarrozin, Abdul; Janah, Tutik Nurul (Santri: Journal of Pesantren and Fiqh Sosial, 2024)
Anti-religious radicalism means efforts to reject radical religious movements. The anti-religious radicalism movement requires synergy between elements of society, religious communities and the government. Pesantren which are often stigmatized as the basis of religious radicalism movements, need to fight this stigma. Therefore, it is hoped that the state will also have an anti-religious radicalism attitude, as seen in Law No. 18/2019 articles about Pesantren. This qualitative research uses a descriptive method with a normative juridical analysis approach. This article aims to understand the articles that support anti-religious radicalism in Law No. 18/2019. The state's partiality in supporting the anti-religious radicalism movement can be read from eight articles in Law No. 18/2019. These eight articles can become the basis for regulations that prevent the emergence of Pesantren as a basis for radical movements.